The Future of Work: Navigating the Challenges and Opportunities of Automation, Gig Economy, and Skills Evolution in a Post-Pandemic World - Anas Romzy Hibrida; Sunarni (West Science Interdisciplinary Studies, 2023)
The landscape of work is undergoing profound transformations worldwide, driven by technological advancements, shifting economic paradigms, and the enduring impact of the COVID-19 pandemic. This research explores the challenges and opportunities arising from automation, the gig economy, skills evolution, and post-pandemic work trends in the context of Indonesia. A mixed-methods approach was employed, combining quantitative data collected through an online survey and qualitative insights gathered from semi-structured interviews with key stakeholders. The findings reveal that automation's impact is perceived as a mixture of opportunities and challenges, with education influencing expectations. The gig economy offers flexibility and supplemental income but raises concerns about job insecurity and benefits. Skills evolution is deemed critical, yet active reskilling efforts remain limited. Remote work trends have accelerated, with hybrid work models emerging as a potential solution to maintain flexibility while addressing challenges. The implications of these findings highlight the need for collaborative efforts among policymakers, businesses, and educational institutions to foster an adaptive and resilient workforce equipped for the evolving world of work.